Millennials’ Expectations of Life at the University and the Workplace: A Malaysian Perspective - Humaira, Raslie; Salina, Pit; Ting, Su Hie (2016)
This study examined the millennial’s expectations of life at the university and the workplace.Questionnaire data were obtained from 142 students aged 20 to 24 in a Malaysian public university from different disciplines. The results showed that most of the participants were highly feedback oriented and expected instant face-to-face feedback from their lecturers, particularly when in emails. They relied on lecture notes to understand the lectures, but would also look for supplementary reading materials. They expected lecturers to deliver interesting lectures but would attend boring lectures to comply with lecture attendance rules. The results also suggest that many participants would not sacrifice their personal time to meet either assignment or work deadlines because they expected deadline extensions. Although the participants preferred positive comments, they also expected to be reprimanded for unsatisfactory work performance. They also expected a fair amount of individual work compared to group work at the workplace. The findings suggest that the participants generally had realistic expectations of university and work life.